Effects of conjugated estrogens/bazedoxifene on lipid and coagulation variables: a randomized placebo- and active-controlled trial. Issue 6 (June 2015) - Skouby, Sven O.; Pan, Kaijie; Thompson, John R.; Komm, Barry S.; Mirkin, Sebastian
Abstract: Objective: This study aims to evaluate the effects of conjugated estrogens (CE)/bazedoxifene (BZA) on lipid and coagulation variables in a randomized, double-blind, placebo- and active-controlled phase 3 study of nonhysterectomized postmenopausal women. Methods: The Selective estrogens, Menopause, And Response to Therapy (SMART)-5 trial evaluated the efficacy and safety of CE/BZA in postmenopausal women (N = 1, 843) with menopausal symptoms. Lipid (N = 1, 843) and coagulation (N = 590) variables were assessed in women receiving daily CE 0.45 mg/BZA 20 mg, CE 0.625 mg/BZA 20 mg, BZA 20 mg, CE 0.45 mg/medroxyprogesterone acetate (MPA) 1.5 mg, or placebo for 12 months. Results: At 12 months, CE 0.45 mg/BZA 20 mg, CE 0.625 mg/BZA 20 mg, BZA 20 mg, and CE 0.45 mg/MPA 1.5 mg decreased total cholesterol and low-density lipoprotein cholesterol compared with placebo ( P < 0.01 for all). Both CE/BZA doses and CE/MPA increased high-density lipoprotein cholesterol compared with placebo ( P < 0.05 for all). CE 0.45 mg/BZA 20 mg had a neutral effect on triglycerides; CE 0.625 mg/BZA 20 mg and CE/MPA increased triglycerides compared with placebo ( P < 0.05). Both CE/BZA doses were associated with small but significant effects on hemostasis variables, including reductions in antithrombin, plasminogen activator inhibitor-1, and fibrinogen activity, and an increase in plasminogen activity relative to placebo at 12 months. Incidences of cardiovascular and venous thromboembolic events were similar among treatment groups. Conclusions: This study provides reassurance that CE/BZA does not adversely affect lipid metabolism or hemostatic balance. In accordance, the incidences of venous thromboembolic events and cardiovascular events in postmenopausal women are similar to those observed with placebo.